PERAN PRAKTIK MODEL PEMBELAJARAN DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU (Study pada Diklat Model-Model Pembelajaran Kota Bekasi tahun 2019) - Emma Himayaturrohmah (Balai Diklat Keagamaan Bandung, 2019)
The problem of this study is the participants' low understanding of learning models and their application in the classroom, especially for Madrasah teachers. The low mastery ability and application of learning models directly influence the lack of effective learning process, and the low interest in learning students. Teacher curriculum demands are required to apply classroom learning models, according to the demands of the 2013 curriculum. The purpose of this study is to find out the participants' understanding of the material of learning models through the application of learning models in the Education and Training Learning Models. This research is a field reserch qualitative descriptive approach. The subjects in this study were Participants in Training Model Learning Models for Madrasah Teachers in Bekasi City, West Java. Data collection techniques were carried out using questionnaires, observation, and documentation studies. The results of the study showed that the mastery of the participants' learning models material improved. This can be seen from the increase in posttest scores from pretest: The lowest value of pretest 12 posttest 28, the highest value of pretest 68 posttest 88, and the average value of pretest 40.93 and posttest 69.47.Key words: Learning models; madrasas teacher; Pretest; Postest